Exposure to Prenatal Infection and Risk of Schizophrenia - Brown, Alan S. (Frontiers Research Foundation, 2011)
We provide a brief review of findings supporting a role for prenatal infection in the etiology of schizophrenia. Our group and others have conducted birth cohort studies to address whether in utero exposure to infectious agents, prospectively documented by biomarker assays of archived maternal sera, and by detailed obstetric records, confer an increased risk of schizophrenia in adult offspring. Prenatal exposure to influenza, elevated toxoplasma antibody, rubella, genital–reproductive infections, and other infections have been associated with an increased risk of schizophrenia among offspring. Animal models have supported these epidemiologic findings by revealing that maternal immune activation causes phenotypes analogous to those found in patients with schizophrenia. Given that exposure to microbial agents are preventable or treatable, they suggest that interventions to diminish the incidence of infection during pregnancy have the potential to prevent an appreciable proportion of schizophrenia cases. Given the clear genetic component to schizophrenia, future studies should include investigations of interactions between prenatal infection and susceptibility genes in the pathogenesis of schizophrenia.